Legal Loophole Related to Ensuring Civil Rights in the Use of Drones With Spying Purposes in Indonesia - Firmansyah, Hery; Oemar, Erwin Natosmal; Putri, Nessya Monica Larasati; Harshita, Harshita (Jurnal Dinamika Hukum, 2024)
Education, economy, and technology are three fields that cannot be separated from the constantly evolving changes. The use of drones as one of the tangible forms of rapid technological development in Indonesia has great potential to cause losses and adverse impacts on national sovereignty. Through this research, the authors will focus on dissecting the legal loophole related to the regulation of drone use that has yet to be comprehensive and has yet to be received attention from the Indonesian people. The guarantee of rights for civil society is an important issue that has yet to be eradicated, especially in terms of the use of drones for spying purposes in Indonesia. This research is a normative juridical research, processing techniques of statutory, conceptual, and comparative approaches. The results of this study state that Indonesia has yet to formulate comprehensive drone regulations, so it is urgent to make detailed rules regarding the classification of drones for recreation and non-recreation/business in order to protect the rights of the affected communities. The research is also compared to a real case in Florida to emphasize the fact that Indonesia is very far away in terms of regulations to protect the rights of its people in terms of the use of drones for spying purposes. This research’s final result and objective focuses on answering the legal vacuum related to guaranteeing civil society’s rights to use drones for spying purposes.